2005
DOI: 10.1007/s11060-004-3014-2
|View full text |Cite
|
Sign up to set email alerts
|

Huge Bilateral Pulmonary and Pleural Metastasis from Intracranial Meningioma: A Case Report and Review of the Literature

Abstract: A case of recurrent meningioma with atypical features and extracranial metastases is reported. A 34-year-old female was operated in 1996, 2000, and 2002, and frontal parasagittal meningioma was extirpated. Histological diagnoses of all the resected tumors were meningotheliomatous meningioma, WHO Grade I. However, 2 years later, the tumor recurred in the frontal scalp and was removed again totally. Histological diagnosis was reported as an atypical meningioma; meningotheliomatous type; WHO Grade II. She receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
51
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 15 publications
1
51
0
Order By: Relevance
“…The histological grade of the tumor is the most important predictive factor of recurrence or metastases 3,6,11 . A review of the histological descriptions of metastatic meningiomas showed that these tumors are predominantly of the papillary, atypical and malignant subtypes 3 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The histological grade of the tumor is the most important predictive factor of recurrence or metastases 3,6,11 . A review of the histological descriptions of metastatic meningiomas showed that these tumors are predominantly of the papillary, atypical and malignant subtypes 3 .…”
Section: Discussionmentioning
confidence: 99%
“…A review of the histological descriptions of metastatic meningiomas showed that these tumors are predominantly of the papillary, atypical and malignant subtypes 3 . However, a high cell proliferation rate is not essential for the occurrence of extracranial metastases and any histologically benign meningioma can possibly metastasize 3,7 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations